Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To find the value of [tex]\( x \)[/tex] for the right-angled triangle with sides [tex]\( (x+5) \)[/tex] cm, [tex]\( (x-3) \)[/tex] cm, and hypotenuse 9 cm, let's use the Pythagorean theorem. The theorem states:
[tex]\[ a^2 + b^2 = c^2 \][/tex]
where [tex]\( a \)[/tex] and [tex]\( b \)[/tex] are the lengths of the legs of the triangle, and [tex]\( c \)[/tex] is the length of the hypotenuse.
Here, [tex]\( a = x + 5 \)[/tex], [tex]\( b = x - 3 \)[/tex], and [tex]\( c = 9 \)[/tex]. Substituting these values into the Pythagorean theorem, we get:
[tex]\[ (x+5)^2 + (x-3)^2 = 9^2 \][/tex]
Now, let's expand and simplify this equation step-by-step.
1. Expand both squared terms:
[tex]\[ (x+5)^2 = x^2 + 10x + 25 \][/tex]
[tex]\[ (x-3)^2 = x^2 - 6x + 9 \][/tex]
2. Add these expanded expressions:
[tex]\[ x^2 + 10x + 25 + x^2 - 6x + 9 = 81 \][/tex]
[tex]\[ 2x^2 + 4x + 34 = 81 \][/tex]
3. Subtract 81 from both sides to set the equation to 0:
[tex]\[ 2x^2 + 4x + 34 - 81 = 0 \][/tex]
[tex]\[ 2x^2 + 4x - 47 = 0 \][/tex]
4. Divide the entire equation by 2 to simplify further:
[tex]\[ x^2 + 2x - 23.5 = 0 \][/tex]
Next, we need to solve this quadratic equation. The solutions to the quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex] can be found using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, [tex]\( a = 1 \)[/tex], [tex]\( b = 2 \)[/tex], and [tex]\( c = -23.5 \)[/tex]. Plugging these values into the quadratic formula:
[tex]\[ x = \frac{-2 \pm \sqrt{(2)^2 - 4(1)(-23.5)}}{2(1)} \][/tex]
[tex]\[ x = \frac{-2 \pm \sqrt{4 + 94}}{2} \][/tex]
[tex]\[ x = \frac{-2 \pm \sqrt{98}}{2} \][/tex]
[tex]\[ x = \frac{-2 \pm 7\sqrt{2}}{2} \][/tex]
[tex]\[ x = -1 \pm \frac{7\sqrt{2}}{2} \][/tex]
This gives us two solutions for [tex]\( x \)[/tex]:
[tex]\[ x = -1 + \frac{7\sqrt{2}}{2} \][/tex]
[tex]\[ x = -1 - \frac{7\sqrt{2}}{2} \][/tex]
Evaluating these to three significant figures:
[tex]\[ x \approx 3.95 \][/tex]
[tex]\[ x \approx -5.95 \][/tex]
Therefore, the values of [tex]\( x \)[/tex] rounded to three significant figures are:
[tex]\[ x \approx 3.95 \][/tex]
[tex]\[ x \approx -5.95 \][/tex]
Both values are valid solutions to the quadratic equation resulting from the given problem.
[tex]\[ a^2 + b^2 = c^2 \][/tex]
where [tex]\( a \)[/tex] and [tex]\( b \)[/tex] are the lengths of the legs of the triangle, and [tex]\( c \)[/tex] is the length of the hypotenuse.
Here, [tex]\( a = x + 5 \)[/tex], [tex]\( b = x - 3 \)[/tex], and [tex]\( c = 9 \)[/tex]. Substituting these values into the Pythagorean theorem, we get:
[tex]\[ (x+5)^2 + (x-3)^2 = 9^2 \][/tex]
Now, let's expand and simplify this equation step-by-step.
1. Expand both squared terms:
[tex]\[ (x+5)^2 = x^2 + 10x + 25 \][/tex]
[tex]\[ (x-3)^2 = x^2 - 6x + 9 \][/tex]
2. Add these expanded expressions:
[tex]\[ x^2 + 10x + 25 + x^2 - 6x + 9 = 81 \][/tex]
[tex]\[ 2x^2 + 4x + 34 = 81 \][/tex]
3. Subtract 81 from both sides to set the equation to 0:
[tex]\[ 2x^2 + 4x + 34 - 81 = 0 \][/tex]
[tex]\[ 2x^2 + 4x - 47 = 0 \][/tex]
4. Divide the entire equation by 2 to simplify further:
[tex]\[ x^2 + 2x - 23.5 = 0 \][/tex]
Next, we need to solve this quadratic equation. The solutions to the quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex] can be found using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, [tex]\( a = 1 \)[/tex], [tex]\( b = 2 \)[/tex], and [tex]\( c = -23.5 \)[/tex]. Plugging these values into the quadratic formula:
[tex]\[ x = \frac{-2 \pm \sqrt{(2)^2 - 4(1)(-23.5)}}{2(1)} \][/tex]
[tex]\[ x = \frac{-2 \pm \sqrt{4 + 94}}{2} \][/tex]
[tex]\[ x = \frac{-2 \pm \sqrt{98}}{2} \][/tex]
[tex]\[ x = \frac{-2 \pm 7\sqrt{2}}{2} \][/tex]
[tex]\[ x = -1 \pm \frac{7\sqrt{2}}{2} \][/tex]
This gives us two solutions for [tex]\( x \)[/tex]:
[tex]\[ x = -1 + \frac{7\sqrt{2}}{2} \][/tex]
[tex]\[ x = -1 - \frac{7\sqrt{2}}{2} \][/tex]
Evaluating these to three significant figures:
[tex]\[ x \approx 3.95 \][/tex]
[tex]\[ x \approx -5.95 \][/tex]
Therefore, the values of [tex]\( x \)[/tex] rounded to three significant figures are:
[tex]\[ x \approx 3.95 \][/tex]
[tex]\[ x \approx -5.95 \][/tex]
Both values are valid solutions to the quadratic equation resulting from the given problem.
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.